2009
DOI: 10.1021/je900716q
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Diffusion of H2S and CO2 in the Ionic Liquid 1-(2-Hydroxyethyl)-3-methylimidazolium Tetrafluoroborate

Abstract: The solubilities and diffusion coefficients of hydrogen sulfide and carbon dioxide gases in the ionic liquid (IL) 1-(2-hydroxyethyl)-3-methylimidazolium tetrafluoroborate ([hemim][BF 4 ]), at temperatures ranging from (303.15 to 353.15) K and pressures up to 1.1 MPa, were determined. The solubility data were correlated using the Krichevsky-Kasarnovsky equation, and Henry's law constants at different temperatures were obtained. From the solubility data, the partial molar thermodynamic functions of solution suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(124 citation statements)
references
References 20 publications
2
122
0
Order By: Relevance
“…In each case a value of R 2 > 0.99 was obtained, which indicates that there exists quite good internal consistency between the experimental data obtained. The Krichevsky-Kasarnovsky equation [28], modified for solvents of negligible vapour pressure [21][22][23], was used to model the experimental results obtained in this work:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In each case a value of R 2 > 0.99 was obtained, which indicates that there exists quite good internal consistency between the experimental data obtained. The Krichevsky-Kasarnovsky equation [28], modified for solvents of negligible vapour pressure [21][22][23], was used to model the experimental results obtained in this work:…”
Section: Resultsmentioning
confidence: 99%
“…Time intervals greater than 2 min were used so that any surface adsorption not in equilibrium with the gas would not affect the values obtained for the diffusion coefficients. The validity of assumptions 1 and 3 has been fully discussed in our previous work [23]. The validity of assumption 2 was checked mathematically for the two systems studied in this work using equation (4) to determine the concentration of the solute at the bottom of the autoclave at the final diffusion time.…”
Section: Apparatus and Proceduresmentioning
confidence: 95%
See 1 more Smart Citation
“…In a subsequent work, they concluded that CO 2 /IL complexations are not the sole controlling factor in relative CO 2 solubility and the energies of vapourisation and molar volumes appear to be determining factors in relative CO 2 solubility in ILs [8]. Later they reported the solubility in the form of Henry's law constants and diffusion of CO 2 at five discrete temperatures from [19] and other [emim] based ILs, which are reported in the literature.…”
Section: Introductionmentioning
confidence: 95%
“…During the present century, a big number of studies have been performed to explore the prospects of ILs for gases separation and for founding the best prototypes for CO 2 capture (Bates et al, 2002, Baltus et al, 2004, Baltus et al, 2005, Shiflett & Yokozeki, 2005, Jacquemin et al, 2006, Hou & Baltus, 2007, . Schilderman et al, 2007, Yokozeki & Shiflett, 2007, Sánchez et al, 2007, Ventura et al, 2008, Camper et al, 2008, Soriano et al, 2008, Soriano et al, 2009, Heintz et al, 2009, a, b. Carvalho et al, 2009, Kuleman et al, 2010, Shokouhi et al, 2010 and also several discoveries have been patented (Brennecke & Maginn, 2002, Davis Jr., 2004, Chinn et al, 2006. Oleffin/paraffin separation is other very important separation process in refineries.…”
Section: Ionic Liquids In Membranes For Selective Gases Separationmentioning
confidence: 99%